Meningkatkan Kemampuan Kerja Sama Pada Siswa Menggunakan Model Sinergi Di Kelas V SDN Alalak Selatan 2 Banjarmasin - Nor Aulia Maulidarrahmah; Aslamiah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Students' inability to work together effectively is the main problem in this research. The SYNERGY learning approach was used to try to fix this problem. Examining student actions, collaboration capacity, and learning outcomes, as well as describing teacher activities are the objectives of this research. This research uses a three-meeting qualitative strategy based on PTK style classroom action research. Fifteen fifth grade students were used as research subjects. Teacher and student actions and their capacity to work together were observed to collect qualitative data. Worksheets, individual and group evaluation forms, and written tests enable the collection of measurable data regarding student learning outcomes. According to the study, teachers met the "Excellent" requirement in all three meetings. Students met the “Almost All Very Active” requirement by increasing their participation from 45% to 91% in sessions I to III. Students' collaborative capacity at meetings I–III increased from 41% to 95%, meeting the requirement of "Almost All Skilled". As a result. The classical completeness rate for student learning outcomes in the cognitive component increased from 59% to 96% between meetings I and III.